Effect of manual therapy combined with Chinese herbal medicine external application in the treatment of ankle sprain (护理手法配合中药外敷治疗踝关节扭伤效果评价) - FEI Mengni (费梦妮); WANG Zhiwei (王志伟) (中西医结合护理)
Objective　Methods Totally 50 patients with ankle sprain were randomly divided into the observation group and control group, with 25 cases in each group. Patients in the control group received routine care, and those in the observation group were given manual therapy combined with Chinese herbal medicine external application. The patient satisfaction was evaluated and compared between two groups. Results The satisfaction rate in the observation group was higher than that in the control group (P＜0. 05). Conclusion The manual therapy combined with Chinese herbal medicine external application is effective for recovery form ankle sprain and improve patients satisfaction. To investigate the effect of manual therapy combined with Chinese herbal medicine external application in the treatment of ankle sprain. (目的 探讨护理手法配合中药外敷治疗踝关节扭伤的效果。方法 选取2021年12月—2022年1月收治的踝关节扭伤患者50例, 随机分为观察组和对照组, 各25例。对照组采用常规护理方法, 观察组采用护理手法配合中药外敷方法。评估并对比两组患者护理满意度。结果 观察组患者满意度高于对照组, 差异有统计学意义(P＜0. 05)。结论 护理手法配合中药外敷干预有利于促进踝关节扭伤患者恢复, 提高患者满意度, 对预防并发症具有积极意义。)